The reductive C3-functionalisation of pyridinium and quinolinium salts through iridium-catalysed interrupted transfer hydrogenation - Grozavu, A; Hepburn, H; Smith, P; Potukuchi, H; Lindsay-Scott, P; Donohoe, T (Springer Nature, 2018)
This paper describes the transformation of flat N-containing aromatic compounds (pyridines and quinolines) into complex 3-dimensional heterocycles bearing new functionality which are ideal for further manipulation. In this reaction methanol and formaldehyde are used as starting materials for the reduction and functionalisation of arenes using an iridium catalyst; thus, inexpensive and renewable feedstocks are utilised in the rapid formation of complex and high value N-heterocycles. By harnessing the in-situ formation of an enamine intermediate, the electrondeficient arene starting materials are converted into nucleophilic species and the C-C bond forming process that follows reverses the normal pattern of reactivity and allows access to the C-3 position of the arene. Mechanistic investigation reveals that formaldehyde is the ultimate source of the hydride added to the arene and further experiments using D-labelled starting materials show the reversible nature of the initial iridum-hydride addition.